Micropropagation and Genetic Fidelity of in vitro Grown Plantlets of Begonia malabarica Lam. - Aswathy J M; Murugan K. (Tropical Life Sciences Research, 2019)
Begonias are ornamental indoor plants and also cultivated for landscaping. Begonia malabarica Lam., found naturally in the hilly regions of South India and Sri Lanka called by the tribals as Narayana Sanjeevi, i.e. possess miraculous therapeutic properties. The present study targets in vitro culture, field establishment and evaluation of its genetic uniformity using anatomical, molecular markers followed by callus induction and establishment of cell suspension. Explants such as shoot tip and leaves from in vitro germinated seeds were cultured on Murashige-Skoog medium. Maximum callus induction was obtained in Murashige-Skoog medium with 0.3 mg L–1 2, 4-D + 0.5 mg L–1 BAP, i.e. 90.8 ± 2.8% with 2.5 ± 0.1 g callus growth. In vitro suspension of cells and their growth rate were also analysed. RAPD and ISSR experiments were carried to confirm the genetic fidelity among in vitro and in vivo plants. Twelve RAPD and seven ISSR primers raised 119 amplicons. Genomic DNA amplification showed similarity between the in vivo and the in vitro generated plantlets. The overall results revealed the uniformity of the in vitro raised B. malabarica plantlets in terms of histoanatomical genetical features and substantiated the assumption that in vitro micropropagation is the secure mode for mass propagation of true to type plants without any somaclonal variations.